(untitled) (Bangladesh Heart Journal, 2021)
Coronary artery disease (CAD) is one of the leading causes of death in our patient population. In the era of cardiovascular intervention, Percutaneous coronary intervention (PCI) is one of the most important modalities in treating these group of patients. Several CAD risks factors and co-morbid conditions are key responsible factor of procedural success. High bleeding risk (HBR) patients undergoing PCI is not an uncommon phenomenon. Incidences and prevalence of HBR patients with CAD and their management by PCI is not well addressed in our literature. PCI in HBR patients carries potential risk of intracranial hemorrhage (ICH) and lifethreatening bleeding. Therefore, careful pre-PCI assessment of possible risk or threats of post-PCI complications in patients with HBR are deem necessitate to understand. We recommend forming multicenter common consensus and to form a guideline in treating HBR patient by PCI. Thus, to reduce post procedural complication and subsequent improvement of mortality and morbidity in HBR patients undergoing PCI in both ST segment elevated myocardial infarction (STEMI) and as well as non-STEMI. Bangladesh Heart Journal 2021; 36(2): 133-138